1)12-(4х+18)=(36+4х)+(18-6х); 2)1,6х-(х-2,8)=(0,2х+1,5)-0,7 3)(0,5х+1,2)-(3,6-4,5х)=(4,8-0,3х)+(10,5х+0,6)

1)12-(4х+18)=(36+4х)+(18-6х); 2)1,6х-(х-2,8)=(0,2х+1,5)-0,7 3)(0,5х+1,2)-(3,6-4,5х)=(4,8-0,3х)+(10,5х+0,6)
Гость
Ответ(ы) на вопрос:
Гость
1)12-(4х+18)=(36+4х)+(18-6х)    12-4х-18=36+4х+18-6х    -6-36-18=4х-2х    -60=2х     -30=х ответ:-30 2)1,6х-(х-2,8)=(0,2х+1,5)-0,7     1,6х-х+2,8=0,2х+1,6-0,7    0,6х-0,2х=0,9-2,8    0,4х=-1,9    х=-4,75 ответ:-4,75 3)(0,5х+1,2)-(3,6-4,5х)=(4,8-0,3х)+(10,5х+0,6)    0,5х+1,2-3,6+4,5х=4,8-0,3х+10,5х+0,6    5х+0,3х-10,5х=2,4+4,8+0,6    -5,2х=7.8     х=-1,5 ответ:-1,5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы